The peacemaker Ronald Reagan, the Cold War, and the world on the brink - Inboden, William 1972- (Dutton, 2022)
"An in-depth and masterful account of how Ronald Reagan's foreign policy "team of rivals" ended the Cold War and laid the foundation for the twenty-first century. Today, the ending of the Cold War seems a foregone conclusion. But in the early 1980s, U.S. intelligence predicted the Soviet Union would last another century. Ronald Reagan entered the White House with no certainty of what would happen next, only an overriding faith in American democracy and an abiding belief that the communist system--and the threat of nuclear war--must be brought to an end. The Peacemaker is the story of the eight years of Reagan's presidency, as he and his foreign policy team managed, in real time, multiple crises around the globe.
Place of publication from publisher's website
Keywords: Reagan, Ronald -- 1911-2004; Geschichte; Entscheidung; Entscheidungsprozess; Ost-West-Konflikt; United States / Foreign relations / 1981-1989; Reagan, Ronald; National security / United States / Decision making / History / 20th century; United States / Foreign relations / Soviet Union; Soviet Union / Foreign relations / United States; Cold War; États-Unis / Relations extérieures / 1981-1989; États-Unis / Relations extérieures / URSS.; URSS / Relations extérieures / États-Unis; Guerre froide; HISTORY / United States / General; Diplomatic relations; National security / Decision making; Soviet Union; United States; 1900-1999; Biography; History; Biographies; Biografie